2015
DOI: 10.1371/journal.pone.0121765
|View full text |Cite
|
Sign up to set email alerts
|

Smyd1 Facilitates Heart Development by Antagonizing Oxidative and ER Stress Responses

Abstract: Smyd1/Bop is an evolutionary conserved histone methyltransferase previously shown by conventional knockout to be critical for embryonic heart development. To further explore the mechanism(s) in a cell autonomous context, we conditionally ablated Smyd1 in the first and second heart fields of mice using a knock-in (KI) Nkx2.5-cre driver. Robust deletion of floxed-Smyd1 in cardiomyocytes and the outflow tract (OFT) resulted in embryonic lethality at E9.5, truncation of the OFT and right ventricle, and additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 63 publications
1
62
0
Order By: Relevance
“…It might be possible that Smyd1a expression is controlled via different mechanisms, for example mechanical overload or hypoxia. In this context, it is already known that Smyd1, together with its interaction partner skNAC (muscle-restricted isoform of the DNA binding protein nascent polypeptide-associated complex) has a crucial role in the response to oxidative and ER stress in the developing mammalian heart [18]. Thus, in zebrafish it might be possible that Smyd1a exhibits the main PKMT activity whereas Smyd1b is mainly responsible for sarcomere organization.…”
Section: Discussionmentioning
confidence: 99%
“…It might be possible that Smyd1a expression is controlled via different mechanisms, for example mechanical overload or hypoxia. In this context, it is already known that Smyd1, together with its interaction partner skNAC (muscle-restricted isoform of the DNA binding protein nascent polypeptide-associated complex) has a crucial role in the response to oxidative and ER stress in the developing mammalian heart [18]. Thus, in zebrafish it might be possible that Smyd1a exhibits the main PKMT activity whereas Smyd1b is mainly responsible for sarcomere organization.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous Smyd1 knockout mice are embryonic lethal at E10.5 and present with severe ventricular hypoplasia and defects in right ventricular formation and trabeculation, associated with transcriptional repression of right ventricular-specific TFs, including Hand2 [83]. Conditional deletion of Smyd1 using the Nkx2.5-Cre driver resulted in defective expansion of second heart field progentiors and reduced cardiomyocyte proliferation [84]. Smyd1 morpholino knockdown in zebrafish embryos also disrupts myofiber maturation [85], further suggesting SMYD1 is essential for cardiac muscle maturation.…”
Section: Histone Methyltrasnferases Are Required For Cardiomyocyte Prmentioning
confidence: 99%
“…SET and MYND domain containing 1 (Smyd1) is a histone methyltransferase specifically expressed in skeletal muscle and myocardium [ 7 , 8 , 9 ]. Smyd1 has been reported to play a crucial regulatory role in differentiation and maturation of skeletal and cardiac muscle cells [ 10 , 11 , 12 ], especially in sarcomere formation and assembly, muscle fibers composition, and myogenesis during cardiogenesis and ventricular development [ 13 ]; however, its role in the adult heart remains poorly understood. It was recently demonstrated that Smyd1 was significantly upregulated in a mouse model of pressure overload-induced HF and that cardiac-specific Smyd1 knockout mice developed cardiomyocyte hypertrophy that led to significant structural remodeling and severe HF [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that Smyd1 was significantly upregulated in a mouse model of pressure overload-induced HF and that cardiac-specific Smyd1 knockout mice developed cardiomyocyte hypertrophy that led to significant structural remodeling and severe HF [ 14 ]. On the other hand, Smyd1 was required for maintaining cardiomyocyte proliferation during the embryonic heart developmental stages and loss of Smyd1 led to lethal consequences [ 11 ]. Moreover, Franklin et al recently suggested a role of Smyd1 as a positive regulator of cardiac metabolism and that activation of Smyd1 can prevent pathological cell growth [ 14 ].…”
Section: Introductionmentioning
confidence: 99%